Carbon-coated heterojunction difunctional electrocatalyst as well as preparation method and application thereof
By preparing carbon-coated heterojunction bifunctional electrocatalysts, the problems of low reserves of precious metal-based catalysts and poor stability of transition metals were solved, and efficient and low-cost hydrogen evolution performance by water electrolysis was achieved, which is suitable for electrocatalytic reactions under alkaline conditions.
Patent Information
- Application Number
- CN202510481551.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-17
- Publication Date
- 2025-09-12
AI Technical Summary
Existing precious metal-based electrocatalysts have low reserves and are expensive, which limits their large-scale industrial applications. Transition metal catalysts have problems with solubility and poor stability in practical applications.
A carbon-coated heterojunction bifunctional electrocatalyst is used. The heterostructure formed by a carbon-coated nickel-based bimetallic alloy derived from a metal organic framework and an oxide is prepared by hydrothermal method and thermal reduction treatment to form a 3D nanosheet composite structure, which improves the conductivity and stability of the catalyst.
The catalyst achieves high intrinsic activity, good conductivity and structural stability. It efficiently catalyzes the electrolysis of water to produce hydrogen under alkaline conditions, is low-cost and easy to mass-produce, and its performance is close to that of commercial Pt catalysts.
Smart Images

Figure CN120625102A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalytic water decomposition catalysts, and in particular to a carbon-coated heterojunction bifunctional electrocatalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen (H2) has attracted widespread attention as an ideal energy carrier that can meet the growing energy demand for economic development. Among the many hydrogen production technologies, electrocatalytic water splitting technology is considered a forward-looking method due to its advantages such as sustainability and zero emissions. However, in this process, ultra-high potential is required to overcome the reaction kinetic energy barrier, so it is necessary to develop efficient catalysts to reduce the overpotential in the reaction. At present, the most advanced electrocatalysts are still precious metals, but the high price and low reserves of precious metals seriously restrict the large-scale overall water splitting application. Therefore, it is extremely important to develop cheap and abundant metal-based catalytic materials to adapt to large-scale and efficient hydrogen and oxygen production.
[0003] Currently, abundant and low-cost 3d transition metals and their corresponding alloys, oxides / hydroxides, sulfides, phosphides, selenides, and nitrides have been extensively studied and are potential alternatives to precious metals. Among them, Ni-based alloys are widely used due to their low cost and the synergistic effects between the metals. Alloying modulates the d-band vacancies of metal catalysts, thereby improving catalytic performance. Nickel-iron alloys, in particular, have demonstrated significant potential for overall hydrolysis. Although breakthroughs have been made in reducing overpotentials for Ni-based alloys, there remains room for improvement in commercial applications. Researchers have developed various strategies to enhance the electrocatalytic performance of Ni-based catalysts, with interfacial engineering being one of the most important. This strategy modulates the electronic structure of the catalyst through heterogeneous coupling effects to optimize the adsorption and desorption of hydrogen intermediates, thereby enhancing the intrinsic activity of the catalyst. Furthermore, long-term operation in alkaline electrolytes and at high overpotentials can lead to agglomeration of metal alloy nanoparticles and metal dissolution, resulting in a loss of active sites and a rapid decline in catalytic activity and stability. The appropriate combination of metal alloys with carbon materials or other conductive materials can significantly enhance electron transport capacity. This is particularly true for carbon-coated electrocatalytic active materials, which not only accelerate electron transfer and correspondingly reduce the energy barrier of intermediates, but also enhance the structural stability of the catalyst. Therefore, based on this technical background, a nickel-based metal alloy / metal oxide heterostructure bifunctional electrocatalyst was developed to achieve efficient alkaline overall hydrolysis reactions. Summary of the Invention
[0004] In order to solve the problem that precious metal-based electrocatalysts in the existing technology are restricted in large-scale industrial application due to their low reserves and high prices; transition metals have been highly valued as a powerful alternative to precious metal-based catalysts. However, transition metals may suffer from dissolution and poor long-term stability in practical applications. The present invention provides a carbon-coated heterojunction bifunctional electrocatalyst and its preparation method and application, aiming to obtain a catalyst with high intrinsic activity, good conductivity and excellent structural stability. Compared with traditional hydrogen production technology, hydrogen production through electrocatalytic water decomposition is more energy-efficient and clean.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned carbon-coated heterojunction bifunctional electrocatalyst, which is simple in process, easy to operate, and convenient for mass production.
[0006] To achieve the above objectives, the present invention provides the following technical solutions:
[0007] A carbon-coated heterojunction bifunctional electrocatalyst is composed of a heterojunction formed by a carbon-coated nickel-based bimetallic alloy derived from a metal organic framework and an oxide (the alloy and the oxide form a heterojunction, and a carbon layer is coated on the outer layer of the alloy). The carbon-coated nickel-based bimetallic alloy derived from the metal organic framework is nanostructured, and the oxide is also nanostructured. The two are stacked to form a 3D nanosheet composite structure supported on a carrier; wherein the carbon-coated nickel-based bimetallic alloy serves as the active phase.
[0008] Preferably, the nickel-based bimetallic alloy is a nickel-based transition metal alloy, and the oxide is a transition metal oxide; the nickel-based transition metal is any two of Ni, Co or Fe, and the transition metal oxide is at least one of W, Mo or V.
[0009] Preferably, the thickness of the metal organic framework-derived carbon-coated nickel-based bimetallic alloy nanostructure is 0.1 to 0.5 μm; and the carrier is nickel foam.
[0010] The method for preparing the carbon-coated heterojunction bifunctional electrocatalyst as described above comprises the following steps:
[0011] (1) mixing the activated support with a transition metal salt, a metal organic ligand, and a mixed solution, and performing a hydrothermal reaction at 90 to 180° C. to grow a metal organic framework (MOF) on the surface of the support;
[0012] (2) placing the metal organic framework (MOF) obtained in step (1) into an aqueous solution containing ammonium molybdate, subjecting it to a hydrothermal reaction at 90-180° C., and washing and drying the resulting product after the reaction is complete to obtain a precursor;
[0013] (3) The precursor obtained in step (2) is subjected to thermal reduction treatment in a reducing atmosphere at 300-450° C. to obtain a MOF-derived carbon-coated heterojunction bifunctional electrocatalyst.
[0014] Preferably, the transition metal salt in step (1) refers to at least one of a halide, nitrate, sulfate, acetate or an oxygen-containing or oxygen-free salt of a transition metal; the nickel-based transition metal is any two of Ni, Co or Fe, and the transition metal oxide is at least one of W, Mo or V; the metal organic ligand in step (1) is terephthalic acid; the final concentration of the transition metal salts after mixing is 0.01 to 0.2 M.
[0015] Preferably, the mixed solution in step (1) is a solution obtained by mixing N,N-dimethylformamide (DMF), alcohol, and water in a volume ratio of N,N-dimethylformamide (DMF): alcohol: water = 10-14:1:1; the alcohol in step (1) is methanol or ethanol; the activated carrier in step (1) is prepared by ultrasonically cleaning the carrier in ethanol for 15 minutes, then activating the carrier with a 3M hydrochloric acid solution for 15 minutes, and finally ultrasonically cleaning the carrier with deionized water for 15 minutes.
[0016] Preferably, the time for the two hydrothermal reactions in step (1) and step (2) is both 4 to 20 hours.
[0017] Preferably, the two hydrothermal reactions in step (1) and step (2) are both carried out at 120° C. for 8 h.
[0018] Preferably, the cleaning and drying in step (2) is to use deionized water and anhydrous ethanol to clean for 3 times each, and then put it into a 60°C oven to dry for 3-4 hours.
[0019] Preferably, the reducing atmosphere described in step (3) is an argon / hydrogen mixed atmosphere; wherein, the volume ratio of argon in the mixed atmosphere is 95%, and the volume ratio of hydrogen is 5%; the time of the thermal reduction treatment described in step (3) is 1 to 3 hours; the thermal reduction treatment described in step (3) is a thermal reduction treatment at 400°C for 2 hours.
[0020] The carbon-coated heterojunction bifunctional electrocatalyst described above is used in the electrolysis of water for hydrogen evolution under alkaline conditions. The catalyst has high intrinsic catalytic activity, abundant active sites, and good electrical conductivity, and can efficiently and stably catalyze the electrolysis of water for hydrogen evolution under alkaline conditions.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The present invention adopts a hydrothermal method to grow a heterogeneous structure electrocatalyst on a nickel foam support. The morphology of the nanosheet structure greatly increases the effective area of the reaction. At the same time, a graphite phase carbon layer derived from a metal organic framework is generated on the outer layer of the nickel-based alloy, which not only solves the inherent defects of the alloy but also helps to improve the conductivity of the material. In addition, a large number of nanopores are generated by dehydration or deamination of the precursor during the heating process, which provides more active sites and further improves the mass transfer performance of the catalyst. After thermal reduction treatment, the catalyst is attached to the support frame in an interconnected nanosheet structure, which is conducive to full contact between the catalyst and the electrolyte and promotes the occurrence of the electrocatalytic reaction, thereby achieving the simultaneous optimization of the three aspects of intrinsic activity, active quantity and conductivity.
[0023] (2) The raw materials used in the present invention are all non-precious substances, the production cost is low, the process is short and easy to operate, and it is convenient for mass production;
[0024] (3) The catalyst obtained by the present invention has high catalytic activity and good durability, and has a catalytic activity comparable to that of commercial Pt catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 These are scanning electron microscope images of the NiFe MOF (a, b) obtained in step (1) of Example 1 of the present invention and the target catalyst MoO2 / NiFe3@C / NF (c, d) obtained in step (3).
[0026] Figure 2 The X-ray diffraction pattern (a) of the target catalyst MoO2 / NiFe3@C / NF obtained in step (3) of Example 1 of the present invention and each comparative catalyst (NiFe3@C, MoO2) and the Raman spectrum of the target catalyst MoO2 / NiFe3@C / NF (b).
[0027] Figure 3 The X-ray photoelectron spectra of the target catalyst MoO2 / NiFe3@C / NF obtained in step (3) of Example 1 of the present invention and the corresponding comparison catalyst are as follows: (a) X-ray photoelectron spectra of the MoO2 / NiFe3@C / NF sample and the NiFe3@C / NF sample in the Ni 2p region; (b) X-ray photoelectron spectra in the Co 2p region; (c) X-ray photoelectron spectra of the MoO2 / NiFe3@C / NF sample in the Mo 3d region; (d) X-ray photoelectron spectra of the MoO2 / NiFe3@C / NF sample in the O1s region; (e) X-ray photoelectron spectra of the MoO2 / NiFe3@C / NF sample in the C1s region.
[0028] Figure 4The present invention provides a target catalyst MoO2 / NiFe3@C / NF obtained in step (3) of Example 1 of the present invention and a comparison diagram of the hydrogen evolution reaction polarization curves (a) and the corresponding Tafel slope diagram (b); a graph showing the relationship between the capacitance current density and the potential sweep rate measured at the open circuit potential of the target catalyst MoO2 / NiFe3@C / NF and the comparison catalysts (NiFe / NF, NiFe3@C / NF, MoO2 / NF, and NF); and a graph showing the impedance spectrum test results of the target catalyst MoO2 / NiFe3@C / NF and the comparison catalysts (d).
[0029] Figure 5 This is a comparison diagram (a) of the oxygen evolution reaction polarization curves of the target catalyst MoO2 / NiFe3@C / NF and the comparative catalysts (NiFe / NF, NiFe3@C / NF, MoO2 / NF, Pt / C / NF, and NF) obtained in step (3) of Example 1 of the present invention; a diagram (c) showing the relationship between the capacitance current density and the potential sweep rate measured at the open circuit potential of the target catalyst MoO2 / NiFe3@C / NF and the comparative catalysts (NiFe / NF, NiFe3@C / NF, MoO2 / NF, and NF); and a diagram (d) showing the impedance spectrum test results of the target catalyst MoO2 / NiFe3@C / NF and the comparative catalysts.
[0030] Figure 6 This is a timing test (a) of the target catalyst MoO2 / NiFe3@C / NF obtained in step (3) of Example 1 of the present invention under HER reaction conditions in 1M KOH; and a timing test (b) under OER reaction conditions. DETAILED DESCRIPTION
[0031] The following is a detailed description of the specific embodiments in conjunction with the accompanying drawings, but it should be understood that the scope of protection of the present invention is not limited by the specific embodiments. The raw materials and reagents used in the examples are all commercially available unless otherwise specified. The nickel foam used in the examples has a thickness of 1.85 mm and a surface density of 620 ± 30 g / m 2 , the aperture is 0.20~0.80mm.
[0032] Example 1
[0033] A method for preparing a carbon-coated heterojunction bifunctional electrocatalyst, the operating steps are as follows:
[0034] (1) Using nickel foam (NF) as a carrier, cut a 4cm×1.5cm nickel foam into a beaker, add ethanol and ultrasonically clean it for 15 minutes, then activate the nickel foam with 3M hydrochloric acid solution for 15 minutes, and finally ultrasonically clean it with deionized water for 15 minutes for use. Weigh 28ml DMF, 2ml anhydrous ethanol, and 2ml deionized water and place them in a 50ml reactor to mix. Then add NiCl2·6H2O (1mmol), FeCl2·4H2O (1mmol) and terephthalic acid (2mmol). After fully dissolving, put the activated nickel foam into the reactor and hydrothermally react at 120℃ for 8h to grow a metal organic framework (MOF) on the surface of the carrier. Cool it naturally to room temperature. The obtained material is fully washed with deionized water and anhydrous ethanol for 3 times and then placed in a vacuum oven at 60℃ for 3 hours to obtain the first step hydrothermal state sample NiFe MOF / NF;
[0035] (2) The first step hydrothermal sample NiFe MOF / NF was placed in a 30 ml aqueous solution containing ammonium molybdate (2 mmol) and placed in a reactor for hydrothermal reaction at 120°C for 8 h. After the reaction, the mixture was cooled to room temperature. The resulting material was taken out and thoroughly washed with deionized water and anhydrous ethanol three times each, and then dried in a vacuum oven at 60°C for 3 hours to obtain the second step hydrothermal sample MoOx / NiFe MOF / NF, i.e., the precursor;
[0036] (3) The obtained precursor was then cut into samples of approximately 1×1.5 cm, placed in a quartz boat, and subjected to thermal reduction treatment for 2 h in an argon / hydrogen mixed atmosphere (argon 95 Vt%, hydrogen 5 Vt%) at 400 °C, maintaining a heating rate of 5 °C / min. The sample was then cooled to room temperature to obtain a MOF-derived carbon-coated heterojunction bifunctional electrocatalyst MoO2 / NiFe3@C / NF (target catalyst).
[0037] Pt / C catalyst was commercially available;
[0038] Preparation of comparative catalyst NiFe3@C / NF: The first hydrothermal sample NiFeMOF / NF obtained in step (1) of Example 1 is directly subjected to step (3), that is, the first hydrothermal sample NiFeMOF / NF is obtained according to step (1) of Example 1, and then the obtained hydrothermal sample is cut into approximately 1×1.5 cm samples, placed in a quartz boat, maintained at a heating rate of 5°C / min, and subjected to thermal reduction treatment at 400°C in an argon / hydrogen mixed atmosphere (argon 95Vt%, hydrogen 5Vt%) for 2h, and cooled to room temperature to obtain the comparative catalyst NiFe3@C / NF.
[0039] Preparation of the comparative catalyst MoO2 / NF: Using nickel foam (NF) as a carrier, a 4 cm × 1.5 cm piece of nickel foam was cut and placed in a beaker. Ethanol was added and ultrasonically cleaned for 15 minutes. The nickel foam was then activated with a 3M hydrochloric acid solution for 15 minutes. Finally, it was ultrasonically cleaned with deionized water for 15 minutes and set aside. The prepared nickel foam was then subjected to steps (2)-(3) of Example 1 to obtain the comparative catalyst MoO2 / NF.
[0040] Preparation of comparative catalyst NiFe alloy: Using nickel foam (NF) as a carrier, cut 4 cm × 1.5 cm of nickel foam and put it into a beaker, add ethanol and ultrasonically clean it for 15 minutes, then activate the nickel foam with 3M hydrochloric acid solution for 15 minutes, and finally ultrasonically clean it with deionized water for 15 minutes and set aside. 32 ml of deionized water was weighed and placed in a 50 ml reactor for mixing. NiCl2·6H2O (1 mmol) and FeCl2·4H2O (1 mmol) were then added and fully dissolved. Activated nickel foam was then placed in the reactor for hydrothermal reaction at 120°C for 8 h. The mixture was naturally cooled to room temperature. The obtained material was washed three times with deionized water and three times with anhydrous ethanol, and then dried in a vacuum oven at 60°C for 3 h to obtain NiFe LDH. The obtained NiFe LDH was cut into samples of approximately 1×1.5 cm and placed in a quartz boat. The heating rate was maintained at 5°C / min, and the samples were thermally reduced in an argon / hydrogen mixed atmosphere (argon 95Vt%, hydrogen 5Vt%) at 400°C for 2 h. The samples were then cooled to room temperature to obtain a NiFe alloy (NiFe / NF).
[0041] The scanning electron microscopy images of the hydrothermal sample NiFe MOF / NF (a, b) obtained in step (1) of this embodiment and the target catalyst MoO2 / NiFe3@C / NF (c, d) obtained in step (3) are as follows: Figure 1 shown.
[0042] The X-ray diffraction pattern (a) of the target catalyst MoO2 / NiFe3@C / NF and the corresponding comparative catalyst obtained in step (3) of this embodiment and the Raman spectrum (b) of MoO2 / NiFe3@C / NF are shown in FIG. Figure 2 shown.
[0043] Figure 3X-ray photoelectron spectra of the target catalyst MoO2 / NiFe3@C / NF and the comparative catalyst obtained in step (3) of this embodiment: (a) X-ray photoelectron spectra of the MoO2 / NiFe3@C / NF sample and the NiFe3@C / NF sample in the Ni 2p region; (b) X-ray photoelectron spectra in the Fe 2p region; (c) X-ray photoelectron spectra of the MoO2 / NiFe3@C / NF sample in the Mo 3d region; (d) X-ray photoelectron spectra of the MoO2 / NiFe3@C / NF sample in the O1s region; (e) X-ray photoelectron spectra of the MoO2 / NiFe3@C / NF sample in the C1s region.
[0044] Scanning electron microscope ( Figure 1 a) and b) NiFe MOF can be observed to present a densely packed nanosheet array morphology, where the thickness of the nanosheet is approximately 0.3 μm. Figure 1 c and d are electron microscope images of the target catalyst of the present invention. It can be seen from the figure that the morphology of the catalyst is composed of nanosheets, but the arrangement of the nanosheets has become sparse and needle-shaped nanoparticles have grown on them. According to XRD analysis ( Figure 2 a), the target catalyst is composed of NiFe3 alloy and MoO2 phase. Raman spectroscopy is used to further prove the existence of carbon layer ( Figure 2 b) The characteristic D band and G band belonging to graphite phase carbon can be clearly seen, and the corresponding characteristic peaks are located at 1357 cm -1 and 1593cm -1 , further proving the presence of carbon coating in the catalyst.
[0045] According to X-ray photoelectron spectroscopy ( Figure 3 ), Ni 2p spectrum of target catalyst MoO2 / NiFe3@C / NF ( Figure 3 a) and Fe 2p spectrum ( Figure 3 b) contains Ni 0 and Fe 0 The results show that the NiFe alloy was successfully prepared. It can be observed that the target catalyst MoO2 / NiFe3@C / NF shifted relative to the comparative catalyst NiFe3@C / NF. Figure 3 c is the Mo 3d spectrum of MoO2 / NiFe3@C / NF catalyst, where Mo 4+ , Mo 6+ The signal peak of MoO2 / NiFe3@C / NF catalyst proves the presence of MoO2. Figure 3 d) There are MO, OH - and H2O signal peak. Figure 3e The appearance of C–C / C=C bond signal peaks in the C1S spectrum of the target catalyst proves the existence of MOF-derived graphitic carbon.
[0046] The electrocatalytic performance test of the target catalyst MoO2 / NiFe3@C / NF obtained in this example:
[0047] All electrochemical measurements were performed using a CHI 660E electrochemical analyzer (Shanghai Zhenhua Instrument Co., Ltd.) electrochemical workstation in a standard three-electrode system. In the HER, the nickel foam-supported catalyst was directly used as the working electrode, the graphite rod was used as the counter electrode, and the Hg / HgO electrode (containing 1.0 M KOH) was used as the reference electrode. In the OER, the nickel foam-supported catalyst was directly used as the working electrode, the Pt sheet electrode was used as the counter electrode, and the Hg / HgO electrode (containing 1.0 M KOH) was used as the reference electrode. The potentials were converted to the reversible hydrogen electrode (RHE) scale according to the formula:
[0048] E(RHE)=E(Hg / HgO)+0.924V(HER)
[0049] E(RHE)=E(Hg / HgO)+0.924V–1.23V(OER)
[0050] Linear sweep voltammetry (LSV) was used at 2 mV s -1 The potential was scanned at a scan rate of 100 mV s and the polarization curve was recorded. The long-term stability was measured by the chronic potential (CP) method at different target current densities. -1 Cyclic voltammetry (CV) tests were performed at a scan rate of 100 nm to investigate another electrochemical stability test. All potentials were manually corrected with 90% iR compensation. Electrochemical impedance spectroscopy (EIS) was performed at an overpotential of 10 mA cm -2 The frequency range was 0.1 MHz to 0.1 Hz, and the AC amplitude was 5 mV. The double layer capacitance (Cdl) was measured by CV to estimate the electrochemically active surface area (ECSA). The specific activity of the catalyst was normalized by its ECSA, which was calculated as follows:
[0051] ECSA = Cdl / Cs, where Cdl is the double layer capacitance and Cs is the specific capacitance.
[0052] Hydrogen evolution reaction polarization curve test results ( Figure 4 ab) show that the target catalyst MoO2 / NiFe3@C / NF has excellent HER activity and exhibits activity comparable to that of commercial Pt / C. MoO2 / NiFe3@C / NF only requires a low overpotential of 33 mV to drive 10 mA cm -2The current density of MoO2 / NiFe3@C / NF is 60mV dec. -1 , slightly higher than Pt / C’s 56mV dec -1 , the results showed that the target catalyst had faster catalytic reaction kinetics.
[0053] Figure 4 c is the cyclic voltammetry test of the target catalyst MoO2 / NiFe3@C / NF and the comparative catalyst sample at different scan rates. The double layer capacitance of the MoO2 / NiFe3@C / NF catalyst is 94mF cm -2 The electrochemically active surface area calculated based on the double-layer capacitance is 1567 cm -2 , higher. The results show that the heterogeneous structure formed between the comparative catalyst NiFe3@C and MoO2 and the 3D nanosheet array effectively increase the density of activation sites for the electrocatalytic reaction. According to the impedance spectroscopy test results ( Figure 5 d) The target catalyst, MoO2 / NiFe3@C / NF, exhibits the lowest resistance, indicating the fastest electron transfer rate. This is primarily due to the coupled interface between the NiFe3 alloy and MoO2, which lowers the electron transfer barrier and provides a favorable electron transport pathway, while the metal-organic framework-derived carbon coating also enhances the catalyst's conductivity.
[0054] The OER performance of MoO2 / NiFe3@C / NF and the comparison catalyst were also tested. Figure 5 In ab, the MoO2 / NiFe3@C / NF catalyst only needs the lowest overpotential of 245mV and 275mV to drive 40mAcm -2 and 100mA cm -2 The current density and the smaller Tafel slope indicate that the catalyst surface has a faster reaction kinetic rate. Similar to HER, the EIS test ( Figure 5 c) It can be seen that MoO2 / NiFe3@C / NF has the smallest transfer resistance (0.3Ω). Figure 5 d MoO2 / NiFe3@C / NF still has the highest Cdl value (98mF dec -1 ). This shows that MoO2 / NiFe3@C / NF has the highest ECSA value and the most abundant accessible active sites.
[0055] Stability is also an important indicator for evaluating catalyst performance. The MoO2 / NiFe3@C catalyst was subjected to chronoamperometric durability tests under HER and OER reaction conditions in 1 M KOH (10, 100, and 1000 mA cm-2 The current density was evaluated by chronopotentiometry (CP) test. The results showed that ( Figure 6 ab) Catalyst 10, 100 mA cm -2 Only slight changes were observed during the 50-h chronoamperometric test at the same current density, indicating that the catalyst has excellent long-term stability.
[0056] Example 2
[0057] A method for preparing a carbon-coated heterojunction bifunctional electrocatalyst, the operating steps are as follows:
[0058] (1) Using nickel foam (NF) as a carrier, cut 4cm×1.5cm nickel foam into a beaker, add ethanol and ultrasonically clean it for 15min, then activate the nickel foam with 3M hydrochloric acid solution for 15min, and finally ultrasonically clean it with deionized water for 15min for use. Weigh 28ml DMF, 2ml anhydrous ethanol, and 2ml deionized water and mix them in a 50ml reactor. Then add CoCl2·6H2O (1mmol), FeCl2·4H2O (1mmol) and terephthalic acid (2mmol). After fully dissolving, put the activated nickel foam into the reactor and hydrothermally react at 90℃ for 20h to grow a metal organic framework (MOF) on the surface of the carrier. Cool it naturally to room temperature. The obtained material is fully washed with deionized water and anhydrous ethanol for 3 times and then placed in a vacuum oven at 60℃ for 4 hours to obtain the first step hydrothermal sample CoFe MOF / NF.
[0059] (2) The first step hydrothermal sample CoFe MOF / NF was placed in a 30 ml aqueous solution containing ammonium molybdate (2 mmol) and placed in a reactor for hydrothermal reaction at 90°C for 20 h. After the reaction, the mixture was cooled to room temperature. The resulting material was taken out and thoroughly washed with deionized water and anhydrous ethanol three times each, and then dried in a vacuum oven at 60°C for 4 hours to obtain the second step hydrothermal sample MoOx / CoFe MOF / NF, i.e., the precursor;
[0060] (3) The obtained precursor was then cut into samples of approximately 1×1.5 cm, placed in a quartz boat, and subjected to thermal reduction treatment at 300°C in an argon / hydrogen mixed atmosphere (argon 95Vt%, hydrogen 5Vt%) for 3 h. The samples were cooled to room temperature to obtain a MOF-derived carbon-coated heterojunction bifunctional electrocatalyst MoO2 / CoFe x @C / NF.
[0061] Example 3
[0062] A method for preparing a carbon-coated heterojunction bifunctional electrocatalyst, the operating steps are as follows:
[0063] (1) Using nickel foam (NF) as a carrier, cut a 4cm×1.5cm nickel foam into a beaker, add ethanol and ultrasonically clean it for 15 minutes, then activate the nickel foam with 3M hydrochloric acid solution for 15 minutes, and finally ultrasonically clean it with deionized water for 15 minutes for use. Weigh 24ml DMF, 4ml anhydrous methanol, and 4ml deionized water and mix them in a 50ml reactor. Then add NiCl2·6H2O (1mmol), FeCl2·4H2O (1mmol) and terephthalic acid (2mmol). After fully dissolving, put the activated nickel foam into the reactor and hydrothermally react at 180℃ for 4h to grow a metal organic framework (MOF) on the surface of the carrier. Cool it naturally to room temperature. The obtained material is fully washed with deionized water and anhydrous ethanol for 3 times and then placed in a vacuum oven at 60℃ for 3 hours to obtain the first step hydrothermal state sample NiFe MOF / NF;
[0064] (2) The first step hydrothermal sample NiFe MOF / NF was placed in a 30 ml aqueous solution containing ammonium molybdate (2 mmol) and placed in a reactor for hydrothermal reaction at 180°C for 4 h. After the reaction, the mixture was cooled to room temperature. The resulting material was taken out and thoroughly washed with deionized water and anhydrous ethanol three times each, and then dried in a vacuum oven at 60°C for 3 hours to obtain the second step hydrothermal sample MoOx / NiFe MOF / NF, i.e., the precursor;
[0065] (3) The obtained precursor was then cut into samples of approximately 1×1.5 cm, placed in a quartz boat, and subjected to thermal reduction treatment at 450°C in an argon / hydrogen mixed atmosphere (argon 95Vt%, hydrogen 5Vt%) for 1 h. The samples were cooled to room temperature to obtain a MOF-derived carbon-coated heterojunction bifunctional electrocatalyst MoO2 / NiFe x @C / NF.
[0066] The foregoing descriptions of specific exemplary embodiments of the present invention are for purposes of illustration and description. These descriptions are not intended to limit the invention to the precise forms disclosed, and it is apparent that many variations and modifications are possible in light of the foregoing teachings. The exemplary embodiments have been selected and described for the purpose of explaining the specific principles of the invention and their practical application, thereby enabling those skilled in the art to realize and utilize a variety of exemplary embodiments of the invention and various options and modifications. The scope of the invention is intended to be defined by the claims and their equivalents.
Claims
1. A carbon-coated heterojunction bifunctional electrocatalyst, characterized by: The heterostructure is composed of a carbon-coated nickel-based bimetallic alloy derived from a metal organic framework and an oxide. The carbon-coated nickel-based bimetallic alloy derived from the metal organic framework is a nanostructure, and the oxide is also a nanostructure. The two are stacked to form a 3D nanosheet composite structure loaded on a carrier; wherein the carbon-coated nickel-based bimetallic alloy serves as the active phase.
2. The carbon-coated heterojunction bifunctional electrocatalyst according to claim 1, characterized in that: The nickel-based bimetallic alloy is a nickel-based transition metal alloy, and the oxide is a transition metal oxide; the nickel-based transition metal is any two of Ni, Co or Fe, and the transition metal oxide is at least one of W, Mo or V; the thickness of the metal organic framework-derived carbon-coated nickel-based bimetallic alloy nanostructure is 0.1 to 0.5 μm; and the carrier is nickel foam.
3. The method for preparing the carbon-coated heterojunction bifunctional electrocatalyst according to claim 1 or 2, characterized in that: The steps are as follows: (1) mixing the activated support with a transition metal salt, a metal organic ligand, and a mixed solution, and performing a hydrothermal reaction at 90 to 180° C. to grow a metal organic framework (MOF) on the surface of the support; (2) placing the metal organic framework (MOF) obtained in step (1) into an aqueous solution containing ammonium molybdate, subjecting it to a hydrothermal reaction at 90-180° C., and washing and drying the resulting product after the reaction is complete to obtain a precursor; (3) The precursor obtained in step (2) is subjected to thermal reduction treatment in a reducing atmosphere at 300-450° C. to obtain a MOF-derived carbon-coated heterojunction bifunctional electrocatalyst.
4. The method for preparing the carbon-coated heterojunction bifunctional electrocatalyst according to claim 3, characterized in that: The transition metal salt in step (1) refers to at least one of a halide, nitrate, sulfate, acetate or an oxygen-containing or oxygen-free acid salt of a transition metal; the nickel-based transition metal is any two of Ni, Co or Fe, and the transition metal oxide is at least one of W, Mo or V; the metal organic ligand in step (1) is terephthalic acid; the final concentration of the transition metal salts after mixing is 0.01 to 0.2 M.
5. The method for preparing the carbon-coated heterojunction bifunctional electrocatalyst according to claim 3, characterized in that: The mixed solution in step (1) is a solution obtained by mixing N,N-dimethylformamide (DMF), alcohol, and water in a volume ratio of N,N-dimethylformamide (DMF): alcohol: water = 10-14:1:1; the alcohol in step (1) is methanol or ethanol; the activated carrier in step (1) is prepared by ultrasonically cleaning the carrier in ethanol for 15 minutes, then activating the carrier with a 3M hydrochloric acid solution for 15 minutes, and ultrasonically cleaning the carrier in water for 15 minutes.
6. The method for preparing the carbon-coated heterojunction bifunctional electrocatalyst according to claim 3, characterized in that: The two hydrothermal reactions in step (1) and step (2) are both carried out at 120° C. for 8 h.
7. The method for preparing the carbon-coated heterojunction bifunctional electrocatalyst according to claim 3, characterized in that: The cleaning and drying in step (2) is to wash with water and anhydrous ethanol three times each, and dry at 60°C for 3-4 hours.
8. The method for preparing the carbon-coated heterojunction bifunctional electrocatalyst according to claim 3, characterized in that: The reducing atmosphere described in step (3) is an argon / hydrogen mixed atmosphere; wherein, the volume ratio of argon in the mixed atmosphere is 95%, and the volume ratio of hydrogen is 5%; the time of the thermal reduction treatment described in step (3) is 1 to 3 hours; the thermal reduction treatment described in step (3) is a thermal reduction treatment at 400°C for 2 hours.
9. Use of the carbon-coated heterojunction bifunctional electrocatalyst according to claim 1 or 2, and the carbon-coated heterojunction bifunctional electrocatalyst prepared by the method according to any one of claims 3 to 9, in hydrogen evolution by electrolysis of water under alkaline conditions.